HUBUNGAN PERSEPSI KARYAWAN TERHADAP PROGRAM KESELAMATAN DAN KESEHATAN KERJA DI PT. PLN (PERSERO) PEKANBARU - LPPM Al-Insyirah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2016)
Program K3 is a system that is designed to secure good safety on all personel at work, besides gets also menumbuhkan perception fires an employee that with marks sense K3's program performing can give healthier and more working condition safe and as more understands and be in control of activities that they do. To the effect this research is subject to be know relationship among perception fires an employee to program K3 at PT. PLN (persero) Pekanbaru. This research constitute quantitative research by designs Cross sectional where is independent variable and variable dependennya is analyzed in the period of which coincides on year month of September 2015 one utilizes analisis univariat and bivariate. Analysis is bivariate did by quiz Chi Square . This observational sample taking to utilize tech full scale sampling which is exhaustive employee at PT. PLN (persero) pekanbaru's generating sector that elected as subjek research as much 50 person. Observational result is perception fire an employee to program K3 at PT. PLN (persero) pekanbaru's generating sector which is with Pvalue< 0,05.